DIFFERENCE IN THE SHOOT EXACTNESS PER A FOOTBALL WITH VARYING INTENSITY AND IN THE STATE OF EXHAUSTION - Duško Bjelica (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2009)
A group of young football professionals was shooting at the goal in the same way and from the same distance. Each of the examinees shot ten times in two rounds. In the first round the shot was done by the unpreferred leg in a state of exhaustion and with an optimal intensity. In the second round, the other ten shots were performed by the un- preferred leg in the state of exhaustion, but with maximum intensity. After appropriate statistic processing it was concluded that the maximum intensity significantly determined the increase of the shot precision, what proves the criterion hypothesis.